If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12y + 4x = 3 Reorder the terms: 4x + 12y = 3 Solving 4x + 12y = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12y' to each side of the equation. 4x + 12y + -12y = 3 + -12y Combine like terms: 12y + -12y = 0 4x + 0 = 3 + -12y 4x = 3 + -12y Divide each side by '4'. x = 0.75 + -3y Simplifying x = 0.75 + -3y
| -16x^2+28x+25=0 | | h=-16t^2+100t+3 | | (3x^2)-x+9=0 | | 6v-8=34 | | .31(x+8)=-19 | | 5(2c+d)6(c+2d)= | | -16x^2+28+25=0 | | -50.00+1.00x=0.80(x-100.00) | | 8x^2-3x+32=0 | | 7=3x-5-7-7 | | 0.10+10=0.35x | | 6+y=2x | | 3=-1t | | 12y-4x=3 | | 0.10+10=0.35 | | 8x+12y=1580 | | 4x-1+12x-17= | | 9-3b+6b= | | (X-4)=-8 | | 11p+7p+4p=27 | | Cscx-secx=0 | | 4x^2=20x-28 | | Y=3x(2x-1)(x+3) | | .10(x+7)=30 | | 18=2g | | .25v-.42=.28v-.25 | | -4(x-3)-13=3(x+2) | | V=(10-2x)(8-2x) | | c(3)=15 | | 2x^2=13x+24 | | 6+2x=-6x-90 | | 5x-10+1x+3=8 |